INTERNET SEBAGAI MEDIA PELAPORAN INFORMASI KEUANGAN PADA PERUSAHAAN LQ-45 di BEI - Andriani, Sri (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2010)
Internet as a medium for reporting financial information (Case Study In The LQ-45 in IDX) is the result of research that explore the internet media in the development of accounting information systems. So some of the problems that arise are: (1) Does the LQ-45 firms listed at BEI have the homepage? (2) The extent to which the LQ-45 firms listing in BEI utilizing communication technology developments, particularly the Internet for the purposes of reporting, especially financial information to meet the needs of their stakeholders? By using the framework Pirchegger Wagenhofer (Pirchegger Wagenhofer Framework) for menganilisa websites of each company, then the obtained result of 95% LQ-45 firms have a website and a majority of LQ-45 menggunnakan duplication of information or hard copies of historical reports that changed in the form of hypertext or pdf format. 42% of company stock prices convey information, although the majority of the home page featuring press releases, 40% who perform the update of the information displayed. Use of the majority of applications using JAVA applications (84%) which is supported by the use of hyperlinks and external links in the homepage. In addition, the majority view (interface) of the sample companies are structured properlyKeywords: Internet, Financial Statements